Emotion Regulation, Positive Affect, and Promotive Voice Behavior at Work - Madrid, Hector P. (Frontiers in Psychology, 2020)
Promotive voice is an essential behavior in today’s organizations to facilitate improvements and make constructive changes in the way that work is conducted. Expanding previous research on the individual drivers of voice behavior in organizations, and drawing on theory about emotion regulation, I propose that speaking out with ideas at work is a function of employee emotion regulation and positive affect. Accordingly, results of a weekly diary study, conducted with professionals from diverse organizations and industries, showed that employees using emotion regulation strategies to improve their feelings increases the experience of positive affect at work, while behaviors oriented to worsen their own feelings was negatively related to the same outcome. Positive affect, in turn, increases the likelihood of promotive voice behavior. These results contribute to the voice behavior literature by showing that emotion regulation is an individual factor that participates in the construction of positive affective experiences which is in turn conducive to speaking out with ideas for improvements and changes at work. Furthermore, these findings inform organizational practitioners about the value of training emotion regulation strategies to improve organizational effectiveness.